How gay men's wives in China practice co-cultural communication: Culture, identity, and sensemaking. Issue 1 (2nd January 2020) - Tang, Lu; Meadows, Cui; Li, Hongmei
ABSTRACT: Around 13.6 million heterosexual women in China are married to gay or bisexual men, and they call themselves tongqi . Tongqi belong to both co-cultural groups (as women and wives) and a dominant group (as heterosexuals). Through a narrative analysis of 51 stories told by tongqi, this study examines the co-cultural strategies tongqi use, and identifies two novel co-cultural strategies: self-blaming and enduring. It also examines how tongqi narratively construct their husbands' co-cultural strategies and finds that tongqi often internalize the ideologies (of gender, sexual orientation, marriage, and family) in their sensemaking process and in their communicative responses to their husbands.